PHYSICAL ACTIVITY AS OVERCONSUMPTION (Fiep Bulletin - online, 2011)
The purpose of the text is to demonstrate the place of physical activity with their contemporary discursive practices and behavior to enable the controlled formation of the social body from consumption. For this, and as Foucault says, be taken as facts of this discourse, Musicalized Aerobic Gymnastics (GAM) and the fitness and practical with quality of life and speech.
Keywords: Physical activity; overconsumption and quality of life